The feasibility of low-intensity psychological therapy for depression co-occurring with autism in adults: The Autism Depression Trial (ADEPT) – a pilot randomised controlled trial. (August 2020) - Russell, Ailsa; Gaunt, Daisy M; Cooper, Kate; Barton, Stephen; Horwood, Jeremy; Kessler, David; Metcalfe, Chris; Ensum, Ian; Ingham, Barry; Parr, Jeremy R; Rai, Dheeraj; Wiles, Nicola
Low-intensity cognitive behaviour therapy including behavioural activation is an evidence-based treatment for depression, a condition frequently co-occurring with autism. The feasibility of adapting low-intensity cognitive behaviour therapy for depression to meet the needs of autistic adults via a randomised controlled trial was investigated. The adapted intervention (guided self-help) comprised materials for nine individual sessions with a low-intensity psychological therapist. Autistic adults (n = 70) with depression (Patient Health Questionnaire-9 score ⩾10) recruited from National Health Service adult autism services and research cohorts were randomly allocated to guided self-help or treatment as usual. Outcomes at 10-, 16- and 24-weeks post-randomisation were blind to treatment group. Rates of retention in the study differed by treatment group with more participants attending follow-up in the guided self-help group than treatment as usual. The adapted intervention was well-received, 86% (n = 30/35) of participants attended the pre-defined 'dose' of five sessions of treatment and 71% (25/35) attended all treatment sessions. The findings of this pilot randomised controlled trial indicate that low-intensity cognitive behaviour therapy informed by behavioural activation can be successfully adapted to meet the needs of autistic people. Evaluation of the effectiveness of this intervention in a full scale randomised controlled trial is now warranted.